Changes to country-specific hepatitis A travel vaccination recommendation for UK travellers in 2017—responding to a vaccine shortage in the national context. (March 2019) - Petersen, J.; Freedman, J.; Ford, L.; Gawthrop, M.; Simons, H.; Edelstein, M.; Plunkett, J.; Balogun, K.; Mandal, S.; Patel, D.
Abstract: Objectives: A routine review of hepatitis A travel vaccination recommendations was brought forward in June 2017 due to hepatitis A vaccine shortages and a concurrent outbreak in men who have sex with men (MSM). There were three objectives: first, to document the review process for changing the recommendations for the UK travellers in June 2017. Second, to study the impact of these changes on prescribing in general practice in 2017 compared with the previous 5 years. Third, to study any changes in hepatitis A notifications in June–October 2017 compared with the previous 5 years. Study design: This is an observational study. Methods: Travel vaccination recommendations for countries with either low-risk (<20%) or high-risk (>90%) status according to child hepatitis A seroprevalence were not changed. A total of 67 intermediate-risk countries with existing recommendations for most travellers and with new data on rural sanitation levels were shortlisted for the analysis. Data on child hepatitis A seroprevalence, country income status, access to sanitation in rural areas and traveller volumes were obtained. Information about the vaccine supply was obtained from Public Health England. Changes to the existing classification were made through expert consensus, based on countries' hepatitis A seroprevalence, sanitation levels, level of income, volume of travel and hepatitis A traveller cases. Data on the number of combined and monovalent hepatitis A–containing vaccines prescribed in England, 2012–2017, were obtained from the National Health Service Business Service Authorities. The number of monthly prescriptions for January–September 2017 was compared with the mean number of prescriptions for the same month in the previous 5 years ( t -test, α = 5%, df = 4). The number of hepatitis A cases notified in June–October 2017 not related to the MSM outbreak was compared with the number of notifications in the same months in previous years. Results: A total of 36 countries were downgraded based on good access (80+% of population) to sanitation in rural areas and the intermediate-risk status in terms of child hepatitis A seroprevalence. For these countries, vaccination would only be recommended to travellers staying long term, visiting friends and relatives or staying in areas without good sanitation. There was a significant decline in hepatitis A vaccine prescriptions in June–September 2017, and there was no increase in the number of notifications. Conclusions: Hepatitis A vaccination recommendations for travel were revised in 2017 following a systematic approach to maintain continuity of supply after a hepatitis A vaccine shortage and increased hepatitis A vaccine demand related to a large outbreak. Improved access to good sanitation in rural areas and low seroprevalence estimates among children have led to 36 countries to no longer require vaccination for most travellers. These changes do not seem to have impacted on hepatitis A notifications in England, although further research will be needed to quantify the impact more precisely. Highlights: Hepatitis A travel vaccination recommendations were revised in response to vaccine supply issues. A decrease in GP travel vaccination followed the change in recommendations. The changes do not seem to have impacted hepatitis A notifications.